Delirium education for family caregivers of patients in the intensive care unit: A pilot study - Amanda Wheeler; Elise Bloch; Sarah Blaylock; James Root; Kateriza Ibanez; Kristine Newman; Jose Diarte; Louis P. Voigt (Elsevier, 2023)
Objectives: Delirium, an acute change in mental state, seen in hospitalized older adults is a growing public health concern with implications for both patients and caregivers; however, there is minimal research on educating caregivers about delirium. Utilizing family caregivers to assist with delirium management in acute care settings demonstrates improved health outcomes supporting the need for patient and family centered care. The primary aims of the study were to determine feasibility of implementing a delirium education video for caregivers of patients in an adult oncology intensive care unit and compare delirium knowledge to caregivers in a control group. Methods: A quasi-experimental design comprised of 31 family caregivers of adult patients in an oncology intensive care unit to determine feasibility of implementing a delirium education video. Results: The results demonstrate feasibility of implementing a caregiver education video in-person and virtually. While total delirium knowledge scores were not statistically significant, knowledge gained within the delirium presentation subgroup was significant (p = .05). Conclusion: This study demonstrates feasibility of implementing a caregiver education video and findings support further research in this area. Innovation: Collaborating with caregivers to develop virtual video education for delirium allows for a versatile approach to connect with caregivers to support their caregiving role.